L-theanineによるsolute carrier family 7 member 5発現細胞特異的細胞増殖抑制作用 - 金城, 俊彦; 宇野, 恭介; 倉本, 展行; 米田, 幸雄; 前田, 定秋 (日本薬理学会年会要旨集, 2022)
Theanine is an amino acid found especially in green tea leaves. Theanine acts on the nervous system to relieve stress and assist in the maintenance of natural sleep. Theanine is also reported to have mild anti-cancer effects. However, the molecular mechanisms underlying these potential effects of theanine remain unknown. We evaluated the effect of theanine on cell growth of several neuronal cell lines (NSC-34, Neuro2A, SH-SY5Y), glial cell lines (C8-D1A, U-251MG) and vascular endothelial cell lines (bEnd.3, and HUVEC). Among them, we found that the growth of proliferative NSC-34 mouse motor neuron–like hybrid cells was the most sensitive to be inhibited by theanine and that this inhibition was highly correlated with the expressions of two solute carriers suspected of being theanine transporters: solute carrier family 38 member 1 (Slc38a1, a glutamine transporter) and solute carrier family 7 member 5 (Slc7a5; a glutamine/leucine exchanger). Theanine-mediated inhibition of cell growth in NSC-34 cells was completely mitigated by co-exposure with leucine, suggesting that theanine inhibited cell growth by disrupting Slc7a5-mediated glutamine/leucine exchange.